Examining the wheat seed delivery system in Bihar, India, using a gender lens - Suri, Bhavya; Gartaula, Hom Nath (Informa UK Limited, 2023)
An effective seed system gives all farmers access to quality seed, reliable information, and up-to-date knowledge of improved varieties and seed practices. Despite significant progress in developing improved wheat varieties, many of these improved varieties have not reached the farmers, especially women, poor, and marginalized farmers. Taking the case of a district in Bihar, India, this paper finds that the existing wheat seed delivery system largely ignores the potential of women farmers to play a significant role in seed production, distribution, or adoption; and that farmer feedback mechanisms are almost non-existent, especially among women. Using a small-scale, mixed, inductive, and broad-based research design, the paper suggests measures for gender-responsive seed delivery systems: improved access to information, especially to women and marginal farmers; promoting women-led groups (like JEEViKA) for their better engagement and empowerment; educating village retailers; developing mechanisms for better collaboration with bigger private seed companies; and increased collaboration among seed stakeholders.